PIDANA PENCABUTAN KEMERDEKAAN JANGKA PENDEK DITINJAU DARI TUJUAN PEMIDANAAN DAN RESOSIALISASI NARAPIDANA - Ahmad Basuki (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2006)
Crime is reaction given by State to someone which have proven to make a mistake to conduct doing an injustice. As an instrument, crime dropped pursuant to and considerations of purpose selected so that will bring benefit for punished by self and for society. Therefore construction of crime person have to be given in execution of crime in institute of community. But the effort do not always in line with crime direction. Appearance of Inmate Subculture in convict community and also given by negative stigma is society is reality in life of diffraction convict become trigger of prisonisasi for convict. Side ejects execution crime in institute of community require to get special attention for convict repeal of freedom short-range. So that crime which isn’t it effective correct reach the target of expected crime, not on the contrary.